INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI SISTEM KREDIT SEMESTER (SKS) - Salis Irvan Fuadi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
Education must be responsive, innovative and aspirational in accordance with what is needed by the community. This research describes the learning innovation of Islamic Education through Semester Credit System (SKS). The learning innovation of Islamic Education (PAI) through Semester Credit System (SKS) can be innovated in terms of curriculum, materials, methods and learning evaluation of Islamic Religious Education (PAI). Innovation to curriculum with Semester Credit System with continuous pattern. Innovation of the material is done by dividing the subjects of PAI into 4 subjects consisting of PAI 1 Fikih, PAI 2, Akhlak, PAI 3 Al-Qur'an Hadith and PAI 4 SKI. Innovation of learning methods offered to be applied as a whole in the subjects of Islamic Religious Education is student centered or learning centered on learners and collaborative learning. The learning evaluation innovation is generally done by taking into account and adhering to the characteristics and principles of evaluation development that still refer to the evaluation model or assessment on the curriculum of 2013.